Dynamic properties of luffa cylindrica fiber reinforced bio-composite beam - (:unkn) unknown (JOURNAL VIBROENGINEERING, 2015)
The aim of this study to investigate the dynamic properties of luffa cylindrica fiber reinforced bio-composite as alternative natural composite materials. As dynamic properties resonance frequencies and damping measured both for the bio-composite and chemical composite materials. To able to compare the properties of natural fiber and chemical fiber, used the same matrix to produce the composite materials. Luffa cylindrica fiber and glass fiber were used as reinforcements, and epoxy resin was used as a matrix to make up the composite specimens. As a dynamic test, vibration tests were fulfilled using hummer. All results obviously showed that damping characteristics of Luffa cylindrica composite is higher than glass fiber composite materials. These results demonstrated that, natural fiber materials can be used instead of chemical materials, in absorbing the vibration due to their high damping.
Keywords: luffa cylindrica fiber; bio-composite; vibration; damping; MECHANICAL-PROPERTIES; FLAX-FIBER; BEHAVIOR; SPONGE